Are deep eutectic solvents benign or toxic? - Hayyan, Maan; Hashim, Mohd Ali; Hayyan, Adeeb; Al-Saadi, Mohammed A.; Alnashef, Inas Muen; Mirghani, Mohamed Elwathig Saeed; Saheed, Olorunnisola Kola (Elsevier Inc., 2013)
In continuation of investigation for environmentally benign protocol for new solvents termed deep eutectic solvents (DESs), it is herein reported results concerning the toxicity and cytotoxicity of choline chloride (ChCl) based DESs with four hydrogen bond donors including glycerine, ethylene glycol, triethylene glycol and urea. The toxicity was investigated using two Gram positive bacteria Bacillus subtilis and Staphylococcus aureus, and two Gram negative bacteria Escherichia coli and Pseudomonas aeruginosa. The cytotoxicity effect was tested using the Artemia salina leach. It was found that there was no toxic effect for the tested DESs on all of the studied bacteria confirming their benign effects on these bacteria. Nevertheless, it was found that the cytotoxicity of DESs was much higher than their individual components (e.g. glycerine, ChCl) indicating that their toxicological behavior is different. For our best knowledge this is the first time that toxicity and cytotoxicity of DESs were studied. The toxicity and cytotoxicity of DESs varied depending on the structure of components. Careful usage of the terms non-toxicity and biodegradability must be considered. More investigation on this matter is required.